Ignorance and political irrationality: epistemic problems for democracy - Coelho, Bruno (Sofia, 2023)
In this paper, I discuss some epistemic problems that democracy faces. Initially, I present the argument according to which ignorance and political irrationality substantially affect current democracies. Then, I expose the principles that support an alternative system: epistocracy. According to the epistocrats, we should prefer the institutional structure that tends to produce the best decisions. Furthermore, political decisions are legitimate and authoritative only when produced by a competent body politic in a competent manner and in good faith. After exposing the principles that support epistocracy, I consider some ways of implementing this system. In the last section, I detail an epistemic response to arguments that question the legitimacy of democracy. I argue that the response does not diminish the strength of the criticisms, so the epistemic problems remain an issue to be faced by democrats.
Keywords: democracy; epistocracy; political irrationality; political ignorance